AN INVESTIGATION OF STUDENTS’ QUANTITATIVE REASONING THROUGH MODELING PROCESS - Aydogan Yenmez, Arzu (International Online Journal of Education and Teaching, 2022)
Both in the transition from arithmetic to algebra and in the problem-solving process, quantitative reasoning is seen as a critical instrument for the development of students' mathematical skills. In the development of quantitative thinking, problems based on daily life experiences play a significant role. The mathematical modeling process is critical in generating mathematical solutions to challenges encountered in everyday life. The goal of this study is to look at how students' quantitative reasoning structures change over time as a result of modeling. A case study was used to assess the research's reasoning process. The study included students with poor, moderate, and strong mathematical reasoning abilities. Over the course of five weeks, the participants were exposed to the modeling process as a group once a week. Clinical interviews with the students were done before and after the modeling process in the study. The modeling process was recorded, observation notes were gathered, and the students' solution sheets were collected. The study's data analysis were carried out in two stages: during data collection and after data collection. The findings reveal significant changes in students' quantitative reasoning structures. The study makes crucial recommendations for both theoretical and practical research.